Upgrading Perusahaan untuk Komunikasi Strategi dalam Dakwah - Pamungkas, Yudha Catur; Nurdin, Ali; Purnomo, Ryan (Jayapangus Press, 2024)
Strategic communication has a central role in optimizing the mission of da'wah, especially in the context of a company that focuses on spreading Islamic values. Efforts to improve the performance of da'wah companies require a more systematic and directed approach. One approach that can be used is the use of DISC (Dominance, Influence, Steadiness, Conscientiousness) personality theory, an effective personality measurement tool to understand individual and team characteristics. This research aims to identify how strategic communication in da'wah can be strengthened through the application of DISC theory, both in internal and external communication of the company. The research method used is a qualitative approach with literature study and secondary data analysis. The results of the study show that the implementation of DISC helps companies understand various personality types, thus allowing for a more personalized, relevant, and effective delivery of da'wah messages. In internal communication, DISC facilitates harmonious team collaboration by recognizing individual strengths and challenges. Meanwhile, in external communication, DISC allows companies to develop communication strategies that suit the target audience based on their personality type. The conclusion of this study confirms that the application of DISC personality theory in strategic communication supports da'wah companies to achieve more optimal results, both in terms of internal management and expansion of da'wah influence. Thus, DISC has become a strategic tool for da'wah companies to increase the effectiveness of communication, expand the reach of messages, and strengthen the mission of da'wah in various circles of society.